Underreported Energy Intake Methods with Metabolic Risk Outcomes among Overweight and Obese Teachers in East Coast, Malaysia - Fauziyyah, Hana; Zainuddin, NurZetty Sofia; Vanoh, Divya; Hazizi, Aqilah Hadhirah; Mardhiah, Sri Zulyanti (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
This study compares three methods of detecting EI (Energy Intake) underreporting and examines their associations with body composition measures—such as Body Mass Index (BMI), body fat percentage, and muscle mass—as well as blood test results, including fasting blood sugar and lipid profiles among overweight and obese adults in East Coast, Malaysia. A total of 333 secondary school teachers, aged 20 to 60 years, were recruited using multistage sampling for this cross-sectional study. We collected sociodemographic characteristics, anthropometric measurements, blood pressure, and biochemical parameters using standardized and validated instruments. Dietary intake data were obtained using validated semi-quantitative Food Frequency Questionnaire (FFQ). Underreporting was assessed using the revised-Goldberg method (EI/ Basal Metabolic Rate (BMR) ratio of 1.2 and 0.9, based on the Mifflin-St Jeor equation) and the EI sex-specific <2.5th and >97.5th percentile. The majority of participants were Malay (98.8%), with a mean age of 48.85±6.88 years old. On average, they were classified as overweight (BMI: 29.30±3.74 kg/m²) and had a high waist circumference (91.66±10.40 cm). The discrepancy between the Goldberg EI/BMR<1.2 and EI sex-specific<2.5th and >97.5th percentile method (26.1% vs. 4.8% underreporters) reflects the higher sensitivity but lower specificity of the Goldberg method, which may have led to higher underreporting estimates to the EI sex-specific<2.5th and >97.5th percentile approach. There were significant association (p<0.05) between energy intake and body fat percentages, visceral fat and High-Density Lipoprotein Cholesterol (HDL-C ) for all three EI underreporting methods. Meanwhile, there was significant association (p<0.005) between energy intake and diastolic blood pressure using EI sex-specific percentile. The EI sex-specific <2.5th and >97.5th percentile method shows promising for detecting EI misreporting in overweight and obese adults. However, further research is needed to validate these findings, as the method remains underexplored.